2010
DOI: 10.1007/s00264-010-1186-2
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum vitamin D deficiency and knee osteoarthritis

Abstract: Background Insufficient levels of serum 25-hydroxyvitamin D (25-OHD) influence the knee joint cartilage and lead to development and progression of knee osteoarthritis (OA). The purpose of this study was to determine the status of serum 25-OHD levels in patients with knee OA compared with controls. Methods A total of 148 patients with knee OA and 150 controls were studied. Serum 25-OHD was measured by the ELISA method and concentrations<20 ng/ml were considered as deficient levels. Mann-Whitney U test was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
100
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 20 publications
3
100
1
2
Order By: Relevance
“…14,[16][17][18][19] All these epidemiological suggests that by achieving normal serum vitamin D level may prevent or delay loss of cartilage loss and reduce the pain and other symptoms of OA. [15][16][17][18] Observation from studies on knee osteoarthritis evaluated by Cao et al suggested that serum 25-OH vitamin D level play an important role in structural changes of knee osteoarthritis. 17 In another study done by Bergink et al also, reported three times increased risk of knee OA and disease progress was associated with serum 25-OH vitamin D <20 ng/ml in the Rotterdam Study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…14,[16][17][18][19] All these epidemiological suggests that by achieving normal serum vitamin D level may prevent or delay loss of cartilage loss and reduce the pain and other symptoms of OA. [15][16][17][18] Observation from studies on knee osteoarthritis evaluated by Cao et al suggested that serum 25-OH vitamin D level play an important role in structural changes of knee osteoarthritis. 17 In another study done by Bergink et al also, reported three times increased risk of knee OA and disease progress was associated with serum 25-OH vitamin D <20 ng/ml in the Rotterdam Study.…”
Section: Discussionmentioning
confidence: 99%
“…12,16 In a recent study, decreased serum level of 25-hydroxy vitamin D was reported in a significant proportion of patients with OA of hip and knee joints. 14,[16][17][18][19] All these epidemiological suggests that by achieving normal serum vitamin D level may prevent or delay loss of cartilage loss and reduce the pain and other symptoms of OA. [15][16][17][18] Observation from studies on knee osteoarthritis evaluated by Cao et al suggested that serum 25-OH vitamin D level play an important role in structural changes of knee osteoarthritis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations